An in vitro comparison of flow dynamics of the Magna Ease and the Trifecta prostheses. Issue 2 (3rd March 2020) - Marx, Philipp; Kowalczyk, Wojciech; Demircioglu, Aydin; Shehada, Sharaf-Eldin; Wendta, Hermann; Mourad, Fanar; Thielmann, Matthias; Jakob, Heinz; Wendt, Daniel
Abstract: Objectives: We aimed to compare the in vitro flow dynamics of the Perimount Magna Ease™ (PME) and the Trifecta™ (TF) bioprostheses. Material and methods: A new flow chamber was designed to compare the flow patterns of the PME (Edwards Lifesciences, Irvine, CA, USA) and the TF (SJM, St. Paul, MN, USA) aortic valve prostheses. This new channel offered the possibility of 2D-particle-image-velocimetry (2D-PIV) to completely evaluate the flow field downstream from the aortic valve to the middle of the aortic arch. Maximum average velocities, vorticity, shear strength, maximum orifice diameters and jet flow diameters were analyzed. Valve sizes of 21, 23 and 25 mm were evaluated. Results: Average velocity values, shear strength and vorticities were smaller in the flow field of the TF (maximum average velocity: 0.81 ± 0.03m/s, PME 23 mm vs. 0.7 ± 0.02m/s TF 23 mm, P < .001) under pulsatile flow conditions (70 Hz, 70 mL stroke volume). The evaluation of the upper orifice area revealed bigger maximum diameters during the peak flow phase for the TF, but more leaflet-flutter. Conclusions: Our flow chamber allowed a precise and highly sensitive characterization and comparison of complex fluid dynamics of different aortic valve prostheses. Both the Trifecta™ and the Perimount Magna Ease™ showed a good performance on a high level.